Colon adenocarcinoma associated with renal cell adenoma - Semra PAKER; Bahar KILIÇASLAN; Gülay ÖZBİLİM and Tekinalp GELEN and Okan ERDOĞAN and Şükrü AKTAN and Fahri IŞITAN (Turkish Journal of Gastroenterology, 2019)
-